Numerical Simulation of Appropriate Design for Selecting Tunnel Support Systems in Squeezing Grounds (Tunnel No. 2 in Tabas Coal Mine, Iran) - Mahdis Shekarchizadeh; Mehdi Najafi; Mohammad Fatehi Marji (Advances in Civil Engineering)
Tunnel No. 2 of the mechanized Tabas coal mine and access entry to E5 panel serve as the primary routes for coal extraction from the longwall mining panel. The main objective of this research is to strengthen and select the optimal support system in the area after the intersection of main tunnel No. 2 with the access tunnel E5 panel, using numerical modeling (FLAC 3D software). The results of numerical modeling have indicated that due to coal seam dip and its partial intersection with tunnel No. 2 at the junction of the main tunnel and the eastern access tunnel at levels 2410–2430, along with the presence of the coal seam above this area, there is less rock mass resistance to the induced stresses. Consequently, significant displacements have been occurred in the floor, walls, and roof of the main tunnel. The numerical modeling results indicated displacements of approximately1.4 m in the sidewalls, 0.8 m in the roof, and 1.2 m in the floor, which correlated with the field measurements. The best way to reinforce and optimize the support system was determined by evaluating the supporting effects of mixed support systems, such as truss bolts, flexi bolts, and different steel frames. Therefore, the best support system arrangement was suggested as adding three 6-m-long flexi bolts in the sidewalls and two 3-m-long truss bolts in the tunnel floor, steel frame TH40, eleven 2.7-m rock bolts, and one 9-m cable bolt in the ceiling and walls was proposed. This support system arrangement reduces the tunnel convergence to 90%. This system has been successfully implemented in the mine and reduced the squeezing-related problems to the lowest degree.